2016
DOI: 10.1016/j.celrep.2016.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Optic Atrophy 1 Is Epistatic to the Core MICOS Component MIC60 in Mitochondrial Cristae Shape Control

Abstract: SummaryThe mitochondrial contact site and cristae organizing system (MICOS) and Optic atrophy 1 (OPA1) control cristae shape, thus affecting mitochondrial function and apoptosis. Whether and how they physically and functionally interact is unclear. Here, we provide evidence that OPA1 is epistatic to MICOS in the regulation of cristae shape. Proteomic analysis identifies multiple MICOS components in native OPA1-containing high molecular weight complexes disrupted during cristae remodeling. MIC60, a core MICOS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 47 publications
17
139
0
Order By: Relevance
“…Notably, a loss of OPA1 leads to opening of the CJ allowing Ca 2+ influx from the intermembrane space into the inner cristae. Such Ca 2+ accumulation inside the cristae is known to accompany altered cristae shape [12, 14], impair respiratory chain super-complexes and respiration [6], and increase the susceptibility of the organelle for apoptotic stimuli [11]. Our present data using a targeted genetically encoded fluorescent protein together with MTG revealed that the dynamics of the CM but not the IBM was strongly reduced by depletion of OPA1.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Notably, a loss of OPA1 leads to opening of the CJ allowing Ca 2+ influx from the intermembrane space into the inner cristae. Such Ca 2+ accumulation inside the cristae is known to accompany altered cristae shape [12, 14], impair respiratory chain super-complexes and respiration [6], and increase the susceptibility of the organelle for apoptotic stimuli [11]. Our present data using a targeted genetically encoded fluorescent protein together with MTG revealed that the dynamics of the CM but not the IBM was strongly reduced by depletion of OPA1.…”
Section: Discussionmentioning
confidence: 53%
“…1c). Considering that a knock-down of OPA1 results in a broadening of the CJ [11, 14], our data suggest that cristae dynamics is reduced under conditions of widened CJ (Fig. 1d).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…OPA1 regulates crista junction number and stability and is the sole regulator of cristae junction width (45). Our findings show that TIA proteins posttranscriptionally downregulate OPA1 gene expression through direct regulatory events linked to splicing and translation of OPA1 and through the functional forms of OPA1 associated with proteolytic processing mediated by OMA1.…”
Section: Discussionmentioning
confidence: 67%